Analysis of the Impact of Tax Compliance on Increasing National Revenue - Irma Herliza Rizki; Oky Syahputra; Azman (International Journal For Advanced Research, 2024)
This study examines the impact of tax compliance on national revenue, highlighting the critical role that compliance plays in fostering fiscal stability and economic growth. By analyzing various countries' tax systems, enforcement mechanisms, and taxpayer behaviors, the study identifies key factors that influence tax compliance, such as government transparency, progressive taxation, public trust, and the use of technological innovations in tax administration. The research reveals that countries with higher compliance rates, supported by efficient enforcement and transparent governance, experience significant increases in national revenue. Furthermore, technological advancements, including e-filing systems and automated payment platforms, are found to be instrumental in reducing tax evasion and enhancing collection efficiency. The study also explores the importance of institutional quality and tax morale in shaping taxpayers' willingness to comply. Finally, the role of international cooperation in curbing cross-border tax evasion and improving compliance rates is emphasized. Overall, the findings suggest that strengthening national policies, investing in technology, and fostering global tax cooperation are essential for enhancing tax compliance and ensuring sustainable economic development.